PÉREZ, María Teresa Gallego. “Vida y muerte en el Corpus Hippocraticum”. Ediciones Clásicas: Madrid, 2015, 469 p., ISBN 8478827986. - Rachid, Rodolfo José Rocha (CODEX - Revista de Estudos Clássicos, 2019)
Resenha de PÉREZ, María Teresa Gallego. “Vida y muerte en el Corpus Hippocraticum”. Ediciones Clásicas: Madrid, 2015, 469 p., ISBN 8478827986.